Dual genetic tracing demonstrates the heterogeneous differentiation and function of neuromesodermal progenitors in vivo - Hengwei Jin; Zixin Liu; Jialing Mou; Muxue Tang; Xiuzhen Huang; Kuo Liu; Qianyu Zhang; Kathy O. Lui; Bin Zhou (Proceedings of the National Academy of Sciences, 2025)
In recent decades, the traditional paradigm of three distinct germ layers formed during gastrulation has been revised with the identification of neuromesodermal progenitors (NMPs). These progenitors emerge during gastrulation and contribute to both the neural ectoderm, particularly the spinal cord, and the adjacent paraxial mesoderm [D. Henrique et al. , Development 142 , 2864–2875 (2015); R. J. Garriock et al. , Development 142 , 1628–1638 (2015); E. Tzouanacou et al. , Dev. Cell 17 , 365–376 (2009)]. However, effective genetic tools for lineage tracing and functional assessments of NMPs in vivo are currently lacking. Here, we developed a dual recombinase–mediated genetic system to specifically trace and ablate Brachyury + Sox2 + NMPs. Our genetic tracing and single-cell RNA sequencing analyses revealed that NMPs consist of three distinct unipotent and bipotent progenitor populations that progressively differentiate into neural and mesodermal fates. Genetic depletion of NMPs demonstrated their critical role in trunk and tail formation. This study provides in vivo genetic evidence supporting the heterogeneity of NMPs in terms of cell fate determination and their functional roles in the developing embryo.